THE ROLE OF MONOVALENT IONS IN THE DETERIORATION OF SOME PHYSICAL PROPERTIES OF CALCAREOUS SOILS IN NORTHERN IRAQ - Saja Albarzanjy; Mohamed Al-Obaidi; Hazim Ahmed (Mesopotamia Journal of Agriculture)
Twelve soil samples of different textures and carbonate minerals were selected from the great soil group (Calciortheds) in northern Iraq. In order to describe the effect of the concept of mono cations ratios (potassium and sodium) responsible for the stability of soil aggregates CROSS as an alternative to the concept of sodium adsorption ratio, on the water conductivity and the average weighted diameter of soil aggregates, an electrolyte solution consisting of mono cations (potassium and sodium) and divalent cations (calcium and magnesium) with potassium ionic dominance over the rest of the other ionic species was allowed at a concentration of (4.26) mmol.L1/2 to undisturbed soil columns with a diameter of 4cm and a length of 6 cm using the miscible displacement technique under the influence of a constant flow solution pressure of 4cm. For ten successive pore volumes for approximately 16 weeks. The flow of electrolyte solution through the columns led to increasing additions of mono cations (K+) that negatively affected the deterioration of different soil groups by sliding their colloids from the original aggregate, causing dispersion of clay colloids dominated by montmorillonite mineral with high ability to swell and disperse clay particles and sliding organic materials, which led to a decrease in the weighted diameter index from 6.18 to 5.43 mm, which led to the deterioration of the soil and a decrease in its water conductivity for all soils from 3.39 to 1.61 cm.h-1. we suggest that the effect of potassium should be taken into account in evaluating soil structure.